Literatur Review: Aktivitas Antibakteri Terhadap Bakteri Penyebab Gangren Diabetik dari Minyak Atsiri Berbagai Tanaman Herbal - Riska Novianti; Mirhansyah Ardana; Yurika Sastyarina (Proceeding of Mulawarman Pharmaceuticals Conferences, 2020)
Diabetic gangrene is a complication caused by infection due to the presence of a bacteria or a wound inflammatory process associated with diabetes mellitus. One of the therapies given is by taking antibiotics and currently the problem of antimicrobial resistance is a problem that is often faced which makes people start using drugs from natural ingredients. This literature search aims to determine the antibacterial activity of essential oils of various herbal plants against bacteria that cause diabetic gangrene. The method used is literature review with journal searches on indexed journal databases. The results obtained from 12 literature show that the essential oil of a herbal plant that has antibacterial activity against bacteria that cause diabetic gangrene, namely Cymbopogon citratus essential oil, Juglans regia L, Zataria multiflora Boiss, Ocimum gratissimum L, Satureja spicigera, Cinnamomum osmophloeum, a combination of essential oils masoyi and cinnamon, citronella (Cymbopogon bernadus L), jeringau rhizome (Acorus calamus Linn), Piper gibbilimbum C, kaffir lime (Citrus hystrix DC) and clove flower essential oil (Syzygium arimaticum).